Primary stability of different implant macrodesigns in a sinus floor elevation simulated model: an ex vivo study - Mikio Imai; Yoichiro Ogino; Hideaki Tanaka; Kiyoshi Koyano; Yasunori Ayukawa; Takeshi Toyoshima (BMC, 2022)
Abstract Background A novel type of implant (Straumann® BLX implant) has been developed for certain stability from the mechanical and biological aspects and is expected for the implant placement in atrophic maxilla with sinus floor elevation (SFE). Purpose The aim of this study was to evaluate the primary stability in the implants with different macrodesigns in an SFE simulated model. Primary stabilities defined as maximum insertion torque (MIT) and implant stability quotient (ISQ) were compared between this novel type of implant and other types. Materials and Methods Five types of Straumann® 10 mm length implants (Standard Plus; SP, Tapered Effect; TE, Bone Level; BL, Bone Level Tapered; BLT and BLX) and two types of Straumann® 6 mm length implants (SP short, BLX short) were used in this study. Each implant was inserted through 5 mm-thick porcine iliac crest blocks (an SFE simulated model). Primary stability was evaluated by using MIT and ISQ. Results The mean value of MIT for BLX group showed significantly higher values than SP, BL (p < 0.01), and TE (p < 0.05) groups. The mean value of ISQ for BLX group was significantly higher than the other groups (p < 0.01). The mean value of MIT and ISQ for BLX and BLX short group were significantly higher than those for SP and SP short group (p < 0.01). Conclusions In an SFE simulated ex vivo model, BLX group showed the highest values. These results suggest that implant selection can play a crucial role in the achievement of primary stability during SFE and simultaneous implant placement.